Media-Media Pembelajaran Efektif dalam Membantu Pembelajaran Matematika Jarak Jauh - Dewasni Hasiru; Syamsu Qamar Badu; Hamzah B. Uno (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
The study is done with the goal of providing a glimpse of what media is effectively used in assisting remote math. The method used in the study is a qualitative approach with a library study type (library research). Retrieval with a documentary technique that is, locate appropriate literature sources through books, research journals and other sources of information relating to effective long-range learning media in mathematics. To see the effectiveness of media using media indicators in the long-range learning system: (1) create motivation, (2) increase learning yields, (3) make learners remember old knowledge, (4) learners capable of applying the knowledge learned. Research shows the media that can be used in long-distance math study is google classroom, learning video, Whatsapp, and zoom. However, effective media used in long-distance math study is google classroom and learning videos, Whatsapp and zoom is still less effective in the long-distance mathematical learning process